PERCEPTION-REALITY GAP IN THE UTILIZATION OF MATERNAL AND CHILD HEALTH CARE SERVICES AMONG TRIBALS IN WAYANAD DISTRICT, KERALA - K P Rajula Helan (Journal of Management Research and Analysis, 2018)
Reproductive and child health and mortality have been viewed as an indicator of socio-economic wellbeing. In Kerala, there has been a remarkable advancement in the maternal and child health status, but there exists wide disparities in the health care service utilization between different social groups. Though the utilization of maternal and child health care services among tribal communities has been increased, disparities also exist with respect to accessibility of health care services among tribal communities. Even though the Government has launched various programmes to provide more facilities to improve the health conditions of tribal mothers and children, its benefits are deprived to the most neglected sections of society. Lack of knowledge about the health care services and perception of quality of services are the main reasons for lower utilization of services. The maternal education emerges as the single most significant predictor of the utilization of maternal and child health care services and higher the level of maternal education results in improved child survival to a substantial extent. This paper is an attempt to analyse the perception of tribe mothers about maternal and child health care services and its utilization and to find out whether there exists any perception–demand gap in the utilization of such services among tribals in Wayanad Districts of Kerala, a district identified for the Domination of tribals.